Profil Komposisi BTP Campuran, Pelabelan, dan Penggunaannya pada Industri Rumah Tangga Pangan (IRTP) di DKI Jakarta - Apriliani, Baiq Rismaulida (Lembaga Publikasi Ilmiah Nusantara, 2025)
Mixed Food Additives (Bahan Tambahan Pangan/BTP campuran) have been registered with the Indonesian National Agency of Drug and Food Control (BPOM) since 2012. However, specific regulations governing mixed BTPs were only issued in 2016 and came into effect in 2017. To date, no studies have examined the registered mixed BTPs. This research aims to identify the composition and distribution labels of mixed BTPs, evaluate their compliance with existing regulations, and assess their use by Home Industry Food Producers (Industri Rumah Tangga Pangan/IRTP). The study utilizes secondary data comprising the composition of mixed BTPs obtained from BPOM, and primary data in the form of distribution labels collected from supermarkets and baking supply stores in Jakarta. The findings reveal that 78% (494 out of 632) of registered mixed BTPs consist of flavoring and coloring agents. The composition of mixed BTPs is categorized into three groups: (1) primary BTPs, which serve technological functions in the final food product; (2) secondary BTPs, which serve technological functions within the mixed BTP formulation; and (3) other substances that influence the physical form of the mixed BTPs (liquid, solid, powder, or paste/semisolid).